A model for high-mass microquasar jets under the influence of a strong stellar wind - Molina, E. (2019)
High-mass microquasars (HMMQs) are systems from which relativistic jets are launched. At the scales of several times the binary system size, the jets are expected to follow a helical path caused by the interaction with a strong stellar wind and orbital motion. Such a trajectory has its influence on the non-thermal emission of the jets, which also depends strongly on the observing angle due to Doppler boosting effects. We explore how the expected non-thermal emission of HMMQ jets at small scales is affected by the impact of the stellar wind and the orbital motion on the jet propagation. We studied the broadband non-thermal emission, from radio to gamma rays, produced in HMMQ jets up to a distance of several orbital separations, taking into account a realistic jet trajectory, different model parameters, and orbital modulation. The jet trajectory is computed by considering momentum transfer with the stellar wind. Electrons are injected at the position where a recollimation shock in the jets is expected due to the wind impact. Their distribution along the jet path is obtained assuming local acceleration at the recollimation shock, and cooling via adiabatic, synchrotron, and inverse Compton processes. The synchrotron and inverse Compton emission is calculated taking into account synchrotron self-absorption within the jet, free-free absorption with the stellar wind, and absorption by stellar photons via pair production. Asymmetric light curves are obtained owing to the helical trajectory of the jets. The presence of helical shaped jets could be inferred from asymmetries in the light curves, which become noticeable only for large jet Lorentz factors and low magnetic fields. Model parameters could be constrained if accurate phase-resolved light curves from GeV to TeV energies were available.